Adubação verde na produtividade, qualidade e rentabilidade de beterraba e rabanete - Batista, Marcos Antonio Vieira (Universidade Federal Rural do Semi-Árido, 2011)
Two experiments were conducted during the period of October 2009 to February 2010, at the Universidade Federal Rural do Semi-Arido, Mossoró - RN, in order to evaluate the productivity, quality and profitability of the beet and radish under different spontaneous species of the Caatinga and amounts of green manures. The experimental design was a randomized complete block with three replications, with treatments arranged in a factorial 3 x 5. The treatments consisted of the combination of three green manures (scarlet starglory, senna uniflora and rooster tree) with five amounts incorporated into the soil (5.4, 8.8, 12.2, 15.6 and 21.0 t ha- 1 in a dry basis). The characteristics evaluated in both crops were: Total productivity of roots, productivity of commercial roots, dry mass of roots (DMR), dry mass of shoots (DMS), plant height, root diameter, percentage of commercial roots and percentage of scrap roots in radish and classified productivity of roots in beet. In addition, the following post-harvest characteristics were also determined: Anthocyanin (beet), soluble solids (SS), titratable acidity (TA), SS/TA ratio, hydrogenic potential (pH) and firmness of roots. The economic indicators evaluated were: Gross income (GI), net income (NI), rate of return (RR) and profit margin (PM). In the beet, the species studied did not differ in the population of the soil actinomycetes. The population of soil actinomycetes increased with increasing amounts of the species incorporated into the soil. The best productive performance of the beet was obtained when it was fertilized with rooster tree and scarlet starglory in the amount of 21.0 t ha-1. The highest content of soluble solids was observed in plots treated with scarlet starglory. The highest incomes and monetary efficiencies were observed in the highest amount of rooster tree incorporated. In the radish, the highest total and commercial productivity of roots were observed in treatments with scarlet starglory. The largest percentage of commercial roots was 73.6%, obtained in the amount of manure of 21.0 t ha-1. The greatest firmness of roots was observed in the treatments with the rooster tree. The highest incomes and monetary efficiencies were observed in the highest amount of scarlet starglory incorporated of 21.0 t ha-1
Keywords: Raphanus sativus; Beta vulgaris; Calotropis procera; Merremia aegyptia; Senna uniflora; Indicadores agronômicos e econômicos; Raphanus sativus; Beta vulgaris; Calotropis procera; Merremia aegyptia; Senna uniflora; Agronomic and economic indicators; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA